Marketing Strategy To Increase Azura Travel Tour Sales - Seroya Indah, Mira; Aldianto, Leo (The Indonesian Journal of Business Administration, 2016)
Abstract - Azura Travel Tour was established in early of 2014 in Bekasi. The company operates on the tourism sector. Azura Travel Tour focuses on the sales of travel agent system which has full facilities including domestic and international air flight tickets purchasing, train tickets purchasing, hotel reservation, domestic and international tourism packages, Hajj Plus and Umroh Trips, multi-payment and pre-pay credits, documents and packages air shipping which cooperate with Lion Group, airport shuttle, travel bus. In 2015, Azura had 200 million Rupiahs as the numbers of net profit target. However, Azura net profit on January to December 2015 was only reached 43% of the expected target. Moreover, among 136 people who are listed as Azura current total of members, only 51% who conduct the transaction. Azura was analyzing the external and internal issues of the company to figure out the problem solving. The external and internal analysis is using PEST Theory and Porter's 5 Forces, STP Analysis, Marketing Mix, Developing Effective Communication, Channel Management Decision, Purchasing Decision's Factor, Competitor Analysis, Data Exploration, and Questionnaire to 136 members of Azura. The root cause of problems in Azura are less effectiveness in strategies making by the intention of winning over the competitors, the lack of effectiveness in designing strategies on advertising programs, the last one is the lack of effectiveness in managing relationship with Azura members After realizing the existing root cause, Azura provides the solutions to fix these issues. The strategies which are going to be used are the designing advertising programs based on company promotional intention and constantly measuring the results of advertisement, fixing strategies on the application of marketing mix in order to win the competition among the competitors, keep embracing the members in handling complaints, conducting business motivation, and also rewarding interesting gifts and awards as appreciation according to the accomplishment, then the members will compete to increase their transactions. Azura will focus on the strategies by the intention of achieving better profit target in the next upcoming years in the implementation plan by designing effective strategies on advertising programs, Ads in newspaper media constantly, advertising cooperation with the members, members evaluation, members gathering. By the analysis and proposed improvement strategies, Azura is expected to be able in achieving better profit target of sales in the next upcoming years.Â Keywords: Strategy, Profit, Member, Azura Travel Tour